Dystocia Due to Uterine Torsion with Fetal Hypotrichosis Congenita in a Crossbred Cow - Vinayaga, Senthil Kumar Jawahar; Ruthrakumar, Ravichandran; Gopikrishnan, Duraisamy; Saranya , Thangavel; Bhargav , Shivamurthy (The Indian Journal of Animal Reproduction, 2025)
A full-term pluriparous crossbred cow in its third parity at the last trimester of gestation had shown signs of restlessness with mild straining at the farmer’s house in Namakkal district. All basic physiological parameters were within the normal range. On per vaginal examination, a twist in the dorsal vagina towards the right side was found that was able to reach the fetal parts by passing the hand through the cervix with the presence of a band in the cervical ring. During the rectal examination, it was found that the broad ligament was crossing from the left side to the right side over the cervix. Hence, the case was diagnosed as right side post cervical uterine torsion. After detorsion by Modified Schaffer’s method, a dead congenital hypotrichosis fetus was relieved and the dam had an uneventful recovery.